The Numerical Stability of the $θ$-Method for Delay Differential Equations with Many Variable Delays (Journal of Computational Mathematics, 1999)
This paper deals with the asymptotic stability of theoretical solutions and numerical methods for the delay differential equations (DDEs)where $a, b_1, b_2, ... b_m$ and $y_0 \in C, 0 < λ_m \le λ_{m-1} \le ... \le λ_1
Keywords: Delay differential equation; Variable delays; Numerical stability; $θ$-methods.